Biological Monitoring Method for Urinary Neonicotinoid Insecticides Using LC‐MS/MS and Its Application to Japanese Adults. Issue 6 (19th January 2015) - Ueyama, June; Nomura, Hiroshi; Kondo, Takaaki; Saito, Isao; Ito, Yuki; Osaka, Aya; Kamijima, Michihiro
Abstract : Biological Monitoring Method for Urinary Neonicotinoid Insecticides Using LC‐MS/MS and Its Application to Japanese Adults: Jun UEYAMA, et al . Department of Pathophysiological Laboratory Sciences, Field of Radiological and Medical Laboratory Sciences, Nagoya University Graduate School of Medicine— Objectives: Agricultural use of neonicotinoid (NEO) insecticides has been increasing in recent years, but their biological monitoring methods have been scarcely reported. In this study, we developed and validated a rapid and sensitive method for quantifying urinary NEO concentrations using high‐performance liquid chromatography‐tandem mass spectrometry (LC‐MS/MS). Methods: After phosphate‐induced acidification of a urine sample, urinary NEOs were trapped by a solid‐phase extraction column and eluted with methanol for acetamiprid, imidacloprid, thiacloprid, thiamethoxam, clothianidin and dinotefuran and with an acetonitrile and methanol solution (1:1, v/v) containing 5% NH3 for nitenpyram. Aseparation analysis was performed by LC‐MS/MS within 10 minutes for the sample. This method was applied to first morning urine obtained from 52 Japanese (40.9 ± 10.5 years old, mean ± standard deviation) without occupational NEO exposure. Results: The linear dynamic ranges and their limit of quantification (LOQ, signal to noise ratio=10) levels were 0.3−20 or 50 μg/ l ( r =0.998−0.999) and 0.05−0.36 μg/ l, respectively. The absolute recovery was 64−95%, and the intra‐ and inter‐day precisions were less than 16.4% (relative standard deviation, %RSD). This method was successfully applied for analysis of NEOs in human urine samples obtained from 52 adults. The frequencies of individuals who showed more than LOD levels was above 90% for imidacloprid, thiamethoxam, clothianidin and dinotefuran, more than 50% for acetamiprid and thiacloprid and 29% for nitenpyram. Conclusions: These results indicated that our new method could be applied to biological monitoring of NEO exposure even at environmental exposure levels in Japanese adults without occupational spraying histories.